TEACHING METHODS OF THE SUBJECT TECHNOLOGY (Ta'limning zamonaviy transformatsiyasi, 2024)
The article discusses the methods of teaching the topic “Metal processing technology”, metal processing technology, pouring molten metal, shapes and parameters of metals, metal processing methods.